Streptococcus agalactiae Inhibits Candida albicans Hyphal Development and Diminishes Host Vaginal Mucosal TH17 Response - Yu, Xiao-Yu; Fu, Fei; Kong, Wen-Na; Xuan, Qian-Kun; Wen, Dong-Hua; Chen, Xiao-Qing; He, Yong-Ming; He, Li-Hua; Guo, Jian; Zhou, Ai-Ping; Xi, Yang-Hong; Ni, Li-Jun; et al. (Frontiers in Microbiology, 2018)
Streptococcus agalactiae and Candida albicans often co-colonize the female genital tract, and under certain conditions induce mucosal inflammation. The role of the interaction between the two organisms in candidal vaginitis is not known. In this study, we found that co-infection with S. agalactiae significantly attenuated the hyphal development of C. albicans, and that EFG1-Hwp1 signal pathway of C. albicans was involved in this process. In a mouse model of vulvovaginal candidiasis (VVC), the fungal burden and the levels of pro-inflammatory cytokines, IL-1, IL-6, TNF-α, and IFN-γ showed a dramatic increase on co-infection with S. agalactiae, while the expressions of TH17 T cells and IL-17 in the cervicovaginal lavage fluid were significantly decreased. Our results indicate that S. agalactiae inhibits C. albicans hyphal development by downregulating the expression of EFG1-Hwp1. The interaction between S. agalactiae and C. albicans may attenuate host vaginal mucosal TH17 immunity and contribute to mucosal colonization by C. albicans.